Dams engineering in a social and environmental context - Pepper, A. T. (ICE, 2012)
This book contains the proceedings of the 17th Biennial Conference of the British Dam Society, Dams: Engineering in a Social and Environmental Context, held at the University of Leeds in September 2012. The 45 papers are grouped into seven sections, although many papers cover more than one section topic area. They share the experiences of many professionals involved in managing and designing work on dams and reservoirs, not only in the UK but in countries around the world.